Розвиток теорії вартісного управління стейкхолдерами підприємства в зарубіжних дослідженнях - Перерва, Петро Григорович; Кобєлєва, Тетяна Олександрівна; Косенко, Олександра Петрівна; Кобєлєв, Валерій Миколайович; Матросова, Вікторія Олександрівна (Сумський державний університет, 2021)
У статті доведено, що актуальним напрямком ефективного управління підприємством є використання менеджментом мережевої концепції організації виробничо-комерційної діяльності, в основі якої лежить теорія стейкхолдерів. Цей напрямок наукових досліджень широко обговорюється в зарубіжних економічних виданнях, де вже накопичилася значна кількість інноваційних розробок та пропозицій. Для вітчизняних промислових підприємств є надзвичайно важливим дослідження, узагальнення та використання зарубіжного досвіду в сфері стейкхолдерівської теорії.

Thes article proves that the actual direction of effective enterprise management is the use of network management concept of production and commercial activities, which is based on the theory of stakeholders. This area of research is widely discussed in foreign economic publications, where a significant number of innovative developments and proposals have already accumulated. Research, generalization and use of foreign experience in the field of stakeholder theory are extremely important for domestic industrial enterprises. The purpose of the study is to study the methods of substantiation of theoretical and methodological approaches and practical recommendations for managing relations with stakeholders on the basis of a cost approach, identification and grouping of stakeholders of industrial enterprises taking into account their interests. Achieving this goal is carried out using a conceptual approach to the formation of total value, which includes the value of the industrial enterprise and the value of its stakeholders, who jointly create the overall contribution of this economic entity in achieving society as a whole. The proposed approach differs positively from the conceptual provisions available in the theory of stakeholders and can be based on the theoretical provisions of managing the relationship of an industrial enterprise with its stakeholders on the basis of a cost approach. The implementation of the proposed approach allows an industrial enterprise to rank stakeholders by value, analyze the dynamics of the structure and parameters of flows of material and financial resources of the enterprise and its stakeholders.
Development of the Theory of Cost Management of Stakeholders of the Enterprise in Foreign Researches
Keywords: стейкхолдери; вартість; потоки ресурсів; класифікація; взаємовідносини; алгоритм; промислові підприємства; stakeholders; cost; resource flows; classification; relationships; algorithm; industrial enterprises